Pengaruh Affiliate Marketing dan Diskon Live Tiktok terhadap Minat Beli Konsumen Generasi Z di Kota Bandung (Studi pada Produk Glad2glow) - Pupu Laela Sari; Nur Hayati (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of social commerce has changed the shopping habits of Generation Z consumers in Indonesia, especially on the TikTok Shop platform. This study analyzes the influence of affiliate marketing and TikTok live streaming discounts on Generation Z consumers' purchasing interest in Glad to Glow products in Bandung City. This study applies a quantitative methodology with a purposive sampling approach with 100 Generation Z respondents aged 18 to 28 years from Bandung City. Data were collected through direct questionnaire distribution and analysis was carried out using multiple linear regression using SPSS 21 software. The results of the study prove that affiliate marketing has a positive and significant effect on purchasing interest (t-count = 8.423; p <0.05) with a contribution of 40.4%. Live streaming discounts also have a positive and significant effect on purchasing interest (t-count = 9.099; p <0.05) with a greater contribution of 47.7%. Simultaneously, both variables show a significant effect on purchasing interest (F-count = 67.206; p <0.05) with a contribution of 58.1% to the variation in consumer purchasing interest. This study offers a theoretical perspective on the purchasing behavior of Generation Z consumers and practical suggestions for skincare companies to improve their marketing efforts on TikTok Shop.